Direct Evidence for a Similar Molecular Mechanism Underlying Shaker Kv Channel Fast Inactivation and Clustering. Issue 3 (1st February 2019) - Lewin, Limor; Nirenberg, Valerie; Yehezkel, Rinat; Naim, Shany; Abdu, Uri; Orr, Irit; Yifrach, Ofer
Abstract: The fast inactivation and clustering functions of voltage-dependent potassium channels play fundamental roles in electrical signaling. Recent evidence suggests that both these distinct channel functions rely on intrinsically disordered N- and C-terminal cytoplasmic segments that function as entropic clocks to time channel inactivation or scaffold protein-mediated clustering, both relying on what can be described as a "ball and chain" binding mechanism. Although the mechanisms employed in each case are seemingly analogous, both were put forward based on bulky chain deletions and further exhibit differences in reaction order. These considerations raised the question of whether the molecular mechanisms underlying Kv channel fast inactivation and clustering are indeed analogous. By taking a "chain"-level chimeric channel approach involving long and short spliced inactivation or clustering "chain" variants of the Shaker Kv channel, we demonstrate the ability of native inactivation and clustering "chains" to substitute for each other in a length-dependent manner, as predicted by the "ball and chain" mechanism. Our results thus provide direct evidence arguing that the two completely unrelated Shaker Kv channel processes of fast inactivation and clustering indeed occur according to a similar molecular mechanism. Graphical Abstract: Highlights: Do both Kv channel inactivation and clustering rely on a ball and chain mechanism? A chain-level chimeric channel approach was used to address the apparent analogy. Native inactivation chain variants support channel clustering in a length-dependent manner. Alternatively spliced clustering chains support channel fast inactivation. Kv channel inactivation and clustering rely on analogous mechanisms.